2022
DOI: 10.3389/fimmu.2022.876355
|View full text |Cite
|
Sign up to set email alerts
|

A TP53 Related Immune Prognostic Model for the Prediction of Clinical Outcomes and Therapeutic Responses in Lung Adenocarcinoma

Abstract: TP53 is the most frequently mutated gene in lung adenocarcinoma (LUAD). The tumor immune microenvironment (TIM) is considered a vital factor that influences tumor progression and survival rate. The influence of TP53 mutation on TIM in LUAD has not been fully studied. Here we systematically investigated the relationship and potential mechanisms between TP53 mutation status and immune response in LUAD. We constructed an immune prognostic model (IPM) using immune associated genes, which were expressed differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has been shown that a high density of cytotoxic immune cells, such as CD8 T cells and NK cells, in the tumor microenvironment is correlated with improved outcome in patients with EC 7,8,24 . On the other hand, the presence of resting memory CD4T cells indicates impaired immune response, and is associated with unfavorable prognosis in cases of melanoma, urothelial cancer, thyroid carcinoma, gastric cancer and lung adenocarcinoma 25–28 . While DCs are thought to present tumor‐associated antigens to naive T cells and contribute to an anti‐tumor role, our findings indicated that high levels of activated DCs within the tumor were inversely correlated with densities of CD8 T cells, and predicted worse outcome for patients with EC.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been shown that a high density of cytotoxic immune cells, such as CD8 T cells and NK cells, in the tumor microenvironment is correlated with improved outcome in patients with EC 7,8,24 . On the other hand, the presence of resting memory CD4T cells indicates impaired immune response, and is associated with unfavorable prognosis in cases of melanoma, urothelial cancer, thyroid carcinoma, gastric cancer and lung adenocarcinoma 25–28 . While DCs are thought to present tumor‐associated antigens to naive T cells and contribute to an anti‐tumor role, our findings indicated that high levels of activated DCs within the tumor were inversely correlated with densities of CD8 T cells, and predicted worse outcome for patients with EC.…”
Section: Discussionmentioning
confidence: 62%
“… 7 , 8 , 24 On the other hand, the presence of resting memory CD4T cells indicates impaired immune response, and is associated with unfavorable prognosis in cases of melanoma, urothelial cancer, thyroid carcinoma, gastric cancer and lung adenocarcinoma. 25 , 26 , 27 , 28 While DCs are thought to present tumor‐associated antigens to naive T cells and contribute to an anti‐tumor role, our findings indicated that high levels of activated DCs within the tumor were inversely correlated with densities of CD8 T cells, and predicted worse outcome for patients with EC. Jensen et al 29 reported that higher levels of intratumoral plasmacytoid dendritic cells (CD123+) were ultimately correlated with worse survival, indicating that DCs play a dual role in tumor progression.…”
Section: Discussionmentioning
confidence: 70%